Anthropogenic factors of influence on the morbidity of the dental system of the children's population of Makhachkala - I. N. Osmanov; F. I. Osmanova; T. F. Kosyreva (Эндодонтия Today, 2021)
Relevance. The study of the relationship between the dental morbidity of children in the city of Makhachkala from the anthropogenic impact of a landfill.Materials and methods. The study was based on a survey of children aged 2 to 17 years in three kindergartens and two schools in the city of Makhachkala in the zone of ecological distress. A total of – 420 children were examined, including – 85 of the temporary bite period; – 110 of the replacement bite period and 225 of the permanent bite period. The criteria for the selection of children were the duration of residence in this neighborhood and the presence of the 1st, 2nd, 3rd and 4th health groups. The dental examination included an assessment of the condition of the oral cavity, hard tooth tissues and periodontal tissues using a set of dental instruments according to a generally accepted technique.Results. Studies on the relationship of poor-quality drinking water with a reduced content of fluoride and the prevalence of non-carious lesions of the hard tissues of the teeth revealed that in the city of Makhachkala, a high prevalence of molarincisive enamel hypoplasia was detected in 45.4% of the examined and a multiple form in 31.6%% of systemic hypoplasia, local hypoplasia was noted in 22.1%, segmental hypoplasia was observed in only 4 children from 335 examined. The prevalence of diseases of the oral mucosa is due to a decrease in immunity in an environmentally unfavorable city, due to the unbalanced composition of macro and microelements in drinking water, high content of sulfur oxides, carbon and dioxin-like compounds in the air. The prevalence and development of caries was noted in 75% of the examined children.Conclusions. The high morbidity rate of the children's population in Makhachkala is associated with the anthropogenic impact of solid household waste, poor-quality drinking water, air and indicates the need to develop modern waste disposal technologies and implement recommendations for the organization of preventive and medical-dental care for children from an early age.